Cutaneous Sarcoidosis as a Predictor of Cardiac Sarcoidosis - Norimatsu, Yuta; Yoshizaki, Ayumi; Ohno, Yuki; Mizuno, Yuka; Watanabe, Haruka; Kotani, Hirohito; Matsuda, Kazuki M; Fukayama, Maiko; Kuzumi, Ai; Ebata, Satoshi; et al. (Archives of Clinical and Biomedical Research, 2021)
Background: Sarcoidosis is a relatively rare, systemic granulomatous disease that occurs in approximately 1–40 per 100,000 individuals but affects Japanese people disproportionately. While sarcoidosis may affect any organ, morbidity and mortality is worst for cases of cardiac sarcoidosis, which is also difficult to diagnose. In this study, we investigated whether cutaneous sarcoidosis, particularly cutaneous sarcoidosis of the face, which is visible and more easily diagnosable, can be a predictor for the development of cardiac sarcoidosis. Method: We retrospectively examined patients with cutaneous sarcoidosis seen at the Department of Dermatology at the JR Tokyo General Hospital and the Department of Dermatology at the University of Tokyo Hospital between April 1, 2005 and March 31, 2019. Results: Our study found that sarcoid lesions on the face increased the risk for cardiac sarcoidosis (p = 0.0090, odds ratio 20), whereas, sarcoid lesions on the extremities decreased the risk for cardiac sarcoidosis (p = 0.0387, odds ratio 0.0961). Conclusion: Cutaneous sarcoidosis of the face is a strong predictor of cardiac sarcoidosis.